THE QUALITY TRANSLATION ANALYSIS OF STUDENT QIRĀAH TEXT - Anwar Sanusi (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2019)
The translation results are considered good quality if the translation results can divert messages that are spread from source language into the target language with an accurate, clear, and natural choice of words. The research aimed to identify and determine the level of accuracy of the translation results of the Arabic Language Education Department of Indonesia University of Education. Accuracy can be considered as the suitability or accuracy of the message conveyed between the source language and target language. This research used a qualitative-descriptive-comparative approach with content analysis design. The results of this research indicate that out of the 16 translation data translated, 18 respondents had an average accuracy of each level, consisting of 12.2% highly accurate, 61.1% accurate, 22.2% less accurate, and 4.5% not accurate.